Evaluation of Clients’ Satisfaction towards Primary Health Care Centers Services at Baghdad City - taha, tareq; jabbar, wissam (Iraqi National Journal of Nursing Specialties, 2017)
Objective: To evaluate the client's satisfaction about the services provided in primary health care centers in thecity of Baghdad and its impact on the improvement of services.Methodology: A simple random sample consisting of (200) clients to primary health care centers in the city ofBaghdad, (15-20) clients for each center using a questionnaire to evaluate the client's satisfaction for the serviceand the use of the direct method of interview, which lasts for (6-10) minutes.Results: Results of the study show that the number of men visits to primary health care centers, fewer womenThis indicates that the most important responsibilities of family members and private health care is theresponsibility of women than men, especially in the eastern communities, and have shown that pregnant womenaged between 30-39 years are more visit to primary health care centers due to pregnancy and its complicationsand most satisfaction towards primary health care services. The study reported that the visit rate was higher forthe unemployed, because of the free health services, and were more satisfied with the services provided, and thestudy showed that the Ministry of Health paid great attention by taking care of the buildings and halls in primaryhealth care centers in the city of Baghdad. The efficiency of the prescribed form to evaluate the satisfaction ofvisitors to primary health care centers and found that the form questioner meet 75% of the study.Recommendation:The study recommends an increase community awareness of the importance of primaryhealth care services and that the services provided are not only for women but for men and women alike.Community education towards primary health care, health services and private school administrations to guidestudents and their parents to visit care centers to take advantage of the services provided and the Ministry ofHealth should be based to improving the quality of services provided to women, particularly maternal and childcare